03 Tissue Trail Drives Pulmonary Vascular Remodeling and its Inhibition Reverses Experimental Pulmonary Arterial Hypertension. (20th November 2012) - Hameed, AG; Arnold, ND; Chamberlain, J; Pickworth, J; Newman, CMH; Crossman, DC; Francis, SE; Lawrie, A
Abstract : Background and aims: Pulmonary arterial hypertension (PAH) is a fatal disease characterised by progressive narrowing of pulmonary arterioles, driven by aberrant cellular proliferation. Identifying key pathways in disease pathogenesis is required for the development of new-targeted therapies. We have previously reported Tumour Necrosis Factor (TNF)-Related Apoptosis-Inducing Ligand (TRAIL) immunoreactivity within pulmonary vascular lesions from patients with idiopathic PAH and animal models. Since TRAIL induces endothelial cell apoptosis and smooth muscle cell proliferation, we hypothesised that TRAIL is an important driver of disease in PAH. Methods: Using the Paigen diet-fed ApoE-/- murine model, we first tested whether genetic deletion (ApoE-/-/TRAIL-/-) and/or anti-TRAIL antibody treatment could modulate disease progression. Bone marrow transplantation (BMT) from ApoE-/- into sub lethally irradiated ApoE-/-/TRAIL-/- mice, and vice versa was performed. Phenotyping included cardiac catheterisation (Right Ventricular Systolic Pressure) and immunohistological analyses of excised lung tissue. Results: ApoE-/-/TRAIL-/- mice were protected from developing PAH (RVSP 28 mmHg v. 50 mmHg, P<0.001, n=6). Anti-TRAIL antibody treatment of ApoE-/- mice with established disease reversed PAH (RVSP 27 mmHg v. 88mmHg, P<0.05, n=4). Blocking TRAIL significantly decreased cellular proliferation and increased apoptosis within pulmonary arterioles. In chimaeras, only mice with expression of TRAIL restricted to tissue developed significant PAH (Mean RVSP 47 mmHg v. 26 mmHg p<0.01, n=4–6). Mice with TRAIL only expressed by bone marrow derived cells showed no significant signs of PAH. Conclusions: Our studies are the first to determine the importance of TRAIL in the pathogenesis of PAH and demonstrate its potential for translation into a novel therapeutic target.